Amazonia—Music Theatre in Three Parts: A Transcultural Operatic Experience? - Castelões Gama, Vítor; Velloso Garcia, Marcelo (Intermédialités / Intermediality, 2021)
This article discusses Amazonia—Music Theatre in Three Parts ([AMT] 2010), a collaboration between the Yanomami, Brazilian and German producers as a transcultural form of resistance that touches on issues of transculturation and Indigenous peoples’ culture and portrayal. We argue that AMT claimed legitimation as an opera and publicized the Yanomami’s views about what extractivism is doing to our planet: devastation beyond tipping points. We first discuss how the Yanomami had been portrayed in art before this opera, and then turn to how the operatic form of AMT was perceived by its reviewers; finally, we offer a critique of the reviewers’ arguments against labelling AMT as a transcultural opera, as we believe these arguments are mainly political. This article aims to demonstrate the fluidity of the boundaries between opera and musiktheater, and of what characterizes a transcultural experience.